'It's My Secret Space': The Benefits of Mindfulness for Social Workers. (10th June 2019) - Kinman, Gail; Grant, Louise; Kelly, Susan
Abstract: Social workers are at high risk of job-related stress that can impair their well-being and professional practice. Although organisational support is a fundamental requirement, it has been argued that social workers need to develop emotional resilience to help them manage the demands of the job. This mixed method study examines the effects of an eight-week mindfulness training course on several resources previously found to underpin resilience in social workers (emotional self-efficacy, psychological flexibility, reflective ability and self-compassion) together with aspects of well-being relevant to the role (compassion fatigue, compassion satisfaction and perceived stress). Participants' perceptions of the benefits of mindfulness for their well-being and professional practice are further explored via the content analysis of open-ended questions and semi-structured interviews. Emotional self-efficacy, psychological flexibility and compassion satisfaction increased following the intervention and compassion fatigue and perceived stress were reduced. No significant changes were found in reflective ability and self-compassion. The qualitative data provided greater insight into the potential benefits of mindfulness for the well-being and job performance of social workers and factors that might encourage and discourage its use.